KEMAMPUAN MEMBACA AL-QURAN SISWA DI THAILAND DAN INDONESIA MELALUI METODE QIROATI - Nuraini, Septi; Hasani Syarif, M. Zainul; Asmahasanah, Salati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Qur'anic reading ability is a fundamental competency in Islamic education, encompassing reading fluency, accuracy of makharijul huruf, and the application of tajwid rules. The Qiroati method, as a systematic and sequential approach to Qur'anic reading instruction, has been widely implemented across Islamic educational institutions not only in Indonesia but also in Southeast Asian countries including Thailand. This study aims to describe and compare students' Qur'anic reading ability at Solihuddin School Songkhla, Southern Thailand and SMPIT At-Taufiq Bogor, Indonesia through the implementation of the Qiroati method. A qualitative approach with a comparative study method was employed. Data were collected through observation, in-depth interviews with school principals, Qiroati teachers, and students at both schools, as well as documentation studies. Data credibility was established through source and technique triangulation. The findings reveal similarities between the two schools, namely gradual improvement in Qur'anic reading ability, the development of Qur'anic reading habits, and high student learning motivation. Differences were found in the level of students' Qur'anic reading ability, where SMPIT At-Taufiq Bogor students demonstrated better and more evenly distributed reading skills compared to Solihuddin School students. These differences are influenced by the continuity of Qiroati implementation from primary education level, students' prior ability, and Qur'anic habituation programs at each school. It is recommended that Islamic educational institutions implement the Qiroati method sequentially from an early age and integrate Qur'anic habituation programs as a support for learning.